2,4-Dimethoxy-6-Methylbenzene-1,3-diol, a Benzenoid From Antrodia cinnamomea, Mitigates Psoriasiform Inflammation by Suppressing MAPK/NF-κB Phosphorylation and GDAP1L1/Drp1 Translocation - Chuang, Shih-Yi; Chen, Chi-Yuan; Yang, Shih-Chun; Alalaiwe, Ahmed; Lin, Chih-Hung; Fang, Jia-You (Frontiers in Immunology, 2021)
Antrodia cinnamomea exhibits anti-inflammatory, antioxidant, and immunomodulatory activities. We aimed to explore the antipsoriatic potential of ethanolic extract (AC) and 2,4-dimethoxy-6-methylbenzene-1,3-diol (DMD) derived from A. cinnamomea. The macrophages activated by imiquimod (IMQ) were used as the cell model for examining the anti-inflammatory effect of AC and DMD in vitro. The heatmap of DNA microarray assay revealed a significant reduction of cytokines, chemokines, and GDAP1L1 in the activated macrophages after DMD treatment. A significantly high inhibition of IL-23 and IL-6 by DMD was observed in THP-1 macrophages and bone marrow-derived mouse macrophages. The conditioned medium of IMQ-stimulated macrophages could reduce neutrophil migration and keratinocyte overproliferation. DMD could downregulate cytokine/chemokine by suppressing the phosphorylation of mitogen-activated protein kinases (MAPKs) and NF-κB. We also observed inhibition of GDAP1L1/Drp1 translocation from the cytoplasm to mitochondria by DMD intervention. Thus, mitochondrial fission could be a novel target for treating psoriatic inflammation. A psoriasiform mouse model treated by IMQ showed reduced scaling, erythema, and skin thickening after topical application of AC and DMD. Compared to the IMQ stimulation only, the active compound decreased epidermal thickness by about 2-fold. DMD diminished the number of infiltrating macrophages and neutrophils and their related cytokine/chemokine production in the lesional skin. Immunostaining of the IMQ-treated skin demonstrated the inhibition of GDAP1LI and phosphorylated Drp1 by AC and DMD. The present study provides insight regarding the potential use of DMD as an effective treatment modality for psoriatic inflammation.